Damai Saujana Homestay Agency / Musa Tompang ... [et al.] - Tompang, Musa; Mohamat Isa, Masliana; Ramli, Mohd Hafizan; Ramli, Rohazmi (Faculty of Office Management & Technology, 2004)
Damai Saujana Homestay Agency is one of the agency companies, which promote homestay program. Our company is located at Kampung Endah, which is many attractive beautifui places, the useful plantation such as palm oil and orchid, a handicraft shops, a traditional foods and many activities that will be show to you. With the available price and package that we served, you will feel different natural environment than other places.